Moderate exercise training since adolescence reduces Walker 256 tumour growth in adult rats. (18th June 2019) - Moreira, Veridiana Mota; Almeida, Douglas; da Silva Franco, Claudinéia Conationi; Gomes, Rodrigo Mello; Palma‐Rigo, Kesia; Prates, Kelly Valério; Tófolo, Laize Peron; Malta, Ananda; Francisco, Flávio Andrade; Pavanello, Audrei; Previate, Carina; da Silva Silveira, Sandra; et al.
Abstract : Key points: Cancer growth, cell proliferation and cachexia index can be attenuated by the beneficial programming effect of moderate exercise training, especially if it begins in adolescence. Walker 256 tumour‐bearing rats who started exercise training during adolescence did not revert the basal low glycaemia and insulinaemia observed before tumour cell inoculation. The moderate exercise training improved glucose tolerance and peripheral insulin sensitivity only in rats exercised early in adolescence. The chronic effects of our exercise protocol are be beneficial to prevent cancer cachexia and hold clear potential as a nonpharmacological therapy of insulin sensitization. Abstract: We tested the hypothesis that moderate exercise training, performed early, starting during adolescence or later in life during adulthood, can inhibit tumour cell growth as a result of changes in biometric and metabolic markers. Male rats that were 30 and 70 days old performed a treadmill running protocol over 8 weeks for 3 days week –1, 44 min day –1 and at 55–65% V ̇ O 2 max . After the end of training, a batch of rats was inoculated with Walker 256 carcinoma cells. At 15 days after carcinoma cell inoculation, the tumour was weighed and certain metabolic parameters were evaluated. The data demonstrated that physical performance was better in rats that started exercise training during adolescence according to the final workload and V ̇ O 2 max . Early or later moderate exercise training decreased the cachexia index, cell proliferation and tumour growth; however, the effects were more pronounced in rats that exercised during adolescence. Low glycaemia, insulinaemia and tissue insulin sensitivity was not reverted in Walker 256 tumour‐bearing rats who trained during adolescence. Cancer growth can be attenuated by the beneficial programming effect of moderate exercise training, especially if it begins during adolescence. In addition, improvement in glucose–insulin homeostasis might be involved in this process. Key points: Cancer growth, cell proliferation and cachexia index can be attenuated by the beneficial programming effect of moderate exercise training, especially if it begins in adolescence. Walker 256 tumour‐bearing rats who started exercise training during adolescence did not revert the basal low glycaemia and insulinaemia observed before tumour cell inoculation. The moderate exercise training improved glucose tolerance and peripheral insulin sensitivity only in rats exercised early in adolescence. The chronic effects of our exercise protocol are be beneficial to prevent cancer cachexia and hold clear potential as a nonpharmacological therapy of insulin sensitization.